A Strong cis‐Effect in an Imidazole‐Imidazolium‐Substituted Alkene. Issue 29 (21st April 2017) - Georgiou, Dayne C.; Haghighatbin, Mohammad A.; Hogan, Conor F.; Scholz, Michael S.; Bull, James N.; Bieske, Evan J.; Wilson, David J. D.; Dutton, Jason L.
Abstract: We report the first example of an alkene with two carbon‐bound substituents (imidazole and imidazolium rings) where the Z‐isomer has a greater thermodynamic stability than the E‐isomer which persists in both the gas phase and in solution. Theoretical calculations, solution fluorescence spectroscopy and gas‐phase ion mobility mass spectrometry studies confirm the preference for the Z‐isomer, the stability of which is traced to a non‐covalent interaction between the imidazole lone pair and the imidazolium ring. Abstract : Down the hill : The first example of an acyclic diorganoalkene (a stilbene analogue) where the Z ‐isomer is more stable than the E ‐isomer is described. The origin of the unusual stability of the Z ‐isomer is traced to a noncovalent interaction between the neutral imidazole and the cationic imidazolium ring.